Influence of the Culture Medium in Dose-Response Effect of the Chlorhexidine on Streptococcus mutans Biofilms - Vanessa Salvadego de Queiroz; Renzo Alberto Ccahuana-Vásquez; Alcides Fabiano Tedesco; Luzia Lyra; Jaime Aparecido Cury; Angélica Zaninelli Schreiber (Scientifica)
The aim of this study was to evaluate the influence of culture medium on dose-response effect of chlorhexidine (CHX) on Streptococcus mutans UA159 biofilm and validate the use of the cation-adjusted-Müller-Hinton broth (MH) for the evaluation of antibacterial activity. Ultrafiltered Tryptone-Yeast Extract Broth (UTYEB) was compared against MH and MH with blood supplementation (MHS). For each medium, six groups (n=4) were assessed: two negative control groups (baseline 48 and 120 h) and four experimental groups (0.0001, 0.001, 0.012, and 0.12% CHX). S. mutans biofilm grew on glass slides of each media containing 1% sucrose. After 48 h of growth, biofilms of baseline 48 h were collected and the other groups were treated for 1 min, twice a day, for 3 days, with their respective treatments. The media were changed daily and pH was measured. After 120 h, biofilms were collected and dry weight and viable microorganisms were determined. Results showed CHX dose-response effect being observed in all media for all the variables. However, MH and MHS showed higher sensitivity than UTYEB (p<0.05). We can conclude that the culture medium does influence dose-response effect of CHX on Streptococcus mutans biofilm and that MH can be used for antibacterial activity.